2014
DOI: 10.3989/mc.2014.02913
|View full text |Cite
|
Sign up to set email alerts
|

Modification of strut effectiveness factor for reinforced concrete deep beams strengthened with CFRP laminates

Abstract: This paper proposes a method to modify the strut effectiveness factor in the strut-and-tie model for CFRP-strengthened reinforced concrete deep beams. Two groups of deep beams comprising six ordinary reinforced concrete deep beams and six CFRP-strengthened reinforced concrete deep beams were experimentally tested under the four-point bending configuration. The shear span-to-effective depth ratio of the beams in each group was 0.75, 1.00, 1.25, 1.50, 1.75, and 2.00. The theoretical principal tensile strain in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…(2014) [4] They presented the effect of CFRP-strengthening on the deformation of RC strut in the design of deep beams .they reported that The value of transverse strain of ordinary RC struts remarkably grew faster than that of CFRP strengthened RC struts after the amount of loading was higher than approximately 40-60% of ultimate shear strength of ordinary RC deep beams. M. Panjehpoura et al . (2014) [5] They proposes strut-and-tie model for CFRP-strengthened reinforced concrete deep beams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2014) [4] They presented the effect of CFRP-strengthening on the deformation of RC strut in the design of deep beams .they reported that The value of transverse strain of ordinary RC struts remarkably grew faster than that of CFRP strengthened RC struts after the amount of loading was higher than approximately 40-60% of ultimate shear strength of ordinary RC deep beams. M. Panjehpoura et al . (2014) [5] They proposes strut-and-tie model for CFRP-strengthened reinforced concrete deep beams.…”
Section: Introductionmentioning
confidence: 99%
“…M. Panjehpoura et al . (2014) [5] They proposes strut-and-tie model for CFRP-strengthened reinforced concrete deep beams. They found that that CFRPeditor@iaeme.com strengthening increases the ultimate shear strength of deep beams from 19.60 % to 30.02 % with shear span-to-effective depth ratios of 0.75 to 2.00, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial research was carried out on the application of polymers in concrete [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Batayeneh et al…”
Section: Introductionmentioning
confidence: 99%
“…The dimensions estimation of bottle-shaped strut is essential in design calculations as the mechanical behaviour of strut is mainly influenced by its dimensions [ 2 , 7 , 19 ]. Among the latest publications on the STM and CFRP-strengthened RC deep beams [ 22 24 ] no research focused on the strut deformation subjected to load. Hence, determination of strut deformation under loading is vital for a reliable design.…”
Section: Introductionmentioning
confidence: 99%